Analysis on power loss reduction and voltage profile enhancement of distribution system through optimal allocation of distribted generators - Bhattarai, Bhrigu Raj; Dhami, Sandeep; Karki, Rajkumar (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.